Prepare for the sustainability era: a quantitative risk analysis model for container shipping sustainability-related risks - Zhou, Yusheng (2024)
Environmental, social, and governance (ESG) issues have attracted global stakeholders' attention, reflecting the focus of sustainability development in this sustainability era. Container shipping is confronted with a wide spectrum of sustainability-related risks during the ESG transformation. Theoretically, this research identifies 36 sustainability risks of container shipping, establishes a customised evaluation framework for container shipping sustainability risks, and quantifies the risks regarding their threatening levels. The five most threatening risks are ‘reinforcement of international emission control policy’, ‘global climate change’, ‘shipping equipment failure’, ‘fuel price volatility’, and ‘ship violates the emission control policy in port area’. The results show that the long-term likelihood as well as environmental and profit impacts of sustainability risks are the most important criteria. Managerially, this research shows that environmental risks are generally the most prioritised risks, while social risks are not significantly impactful to container shipping companies. However, among the social risks, seafarer-related risks are worth paying attention.